Thermal and Chemical Inactivation of Bacillus Phage BM-P1 - Xia Chen; Can Zhang; Jing Guo; Xuecheng Huang; Ruirui Lv; Xingyu Quan (Journal of Food Protection, 2024)
Bacillus spp. are often used as probiotics; however, they can be infected by phages, leading to significant economic losses. Biocidal and thermal treatments are considered rapid and effective methods for controlling microbial contamination. To prevent viral contamination in industrial dairy production, the impact of temperature and biocides on the viability of Bacillus methylotrophic phage BM-P1 was assessed. The results demonstrated that reconstituted skim milk (RSM) as a medium showed the most effective protective effect on phage BM-P1. Treatment at 90°C for 5 min or 72°C for 10 min inactivated it to nondetectable levels from the initial titer of 7.19 ± 0.11 log, regardless of the culture medium. Sodium hypochlorite exhibited the best inactivating effect, which could reduce the phage titer below the detection level in 4 min at 50 ppm. Additionally, treatment with 75% ethanol for 20 min or 50% isopropanol for 30 min could achieve inactivation to nondetectable levels. The inactivating effect of peracetic acid was limited; even when treated at the highest concentration (0.45%) for 60 min, only a 2.47 ± 0.17 log reduction was observed. This study may provide some theoretical basis and data support for establishing measures against Bacillus spp. phages.